MUTANT PREVENTION CONCENTRATION OF LEVOFLOXACINALONE AND IN COMBINATION WITH CEFTAZIDIME AGAINSTLEVOFLOXACIN AND CEFTAZIDIME SENSITIVE AND RESISTANTISOLATES OF Pseudomonas aeruginosa - Abdullah, Mohammed; Abdulkareem, Maisem (Iraqi Journal of Science, 2024)
The study includes 23 isolates of Pseudomonas aeruginosa isolated from woundinfections .The Minimum Inhibitory Concentration (MIC) to each of Levofloxacinand Ceftazidime for these isolates were determined. The results showed 11(47.8%)isolates sensitive to both antibiotics, 5(21.7%) isolates resistant to each one of theantibiotics and 7(30.5%) isolates appeared resistance to one of them and sensitive tothe other. Mutant Prevention Concentration (MPC) to both Levofloxacin andCeftazidime alone and in combination were determined to the 5 sensitive and 5resistant isolates to both antibiotics. Mutant Selection Window (MSW) wascalculated according to the data of MPC and MIC to both levofloxacin andCeftazidime alone and in combination to the same isolates which their MPC weredetermined (10 isolates). The decrease in the value of MSW by 1-2 times were notedwhen both antibiotics together (in combination) were used in comparison with itsvalue when Levofloxacin was used alone (before combination) to the sensitiveisolates (5 isolates), and this indicates a synergistic action whereas, no synergisticaction appeared in the resistant isolates (5 isolates) according to the MSW values,this emphasizes that the combination between levofloxacin and ceftazidime againstresistant isolates is useless.